Employing modern digital technology in the design of television advertising (virtual decoration) (Journal of the College of Basic Education, 2022)
The advertisement represents one of the main activities in the field of marketing of goods and services in the modern era because it is a means of transferring ideas and information to people with the aim of changing their opinions, enhancing them or maintaining them. This activity is as old as human dealings, but it has witnessed developments and qualitative leaps that have brought it to the point where it has studies to carry out By it, where we find that its uses and importance have doubled. Where designers have been able today to produce multiple forms of advertisements thanks to the technical and technological development in using methods to design television advertising using computer technologies that facilitated the task of making advertisements with less effort and lower cost through the use of the virtual studio, and chroma, and most designers, directors and producers have resorted to using these technologies For the purpose of employing them in advertisements. Therefore, the researcher resorted to the study by (employing modern technology in the design of television advertising (virtual décor), this research included the problem that was represented by the following question: - (What is the modern technology in the design of television advertising (virtual décor). On the employment of modern technology in the design of television advertising (virtual décor.The researcher defined a set of terms. In order to reach the goal of the research, basic axes were identified, which included: the use of modern technology in advertising, technical development in television decoration, the most important modern technologies for the work of virtual decoration, blue and green backgrounds (chroma), In the research methodology, the researcher adopted a descriptive approach to reach the research objectives, as the research community included virtual studio advertisements displayed on the Internet. (15) advertisements in which the virtual studio technology was presented, out of a total of (50) advertisements with a variety of ideas, i.e. television ads were chosen. Which contains the virtual studio, and by five models, and the ads were chosen to achieve the purposes of the study. Among the most prominent results of the study to analyze the sample forms:1- Digital technologies appeared in all advertising models, which were characterized by the use of chroma (green or blue screen) and how to use digital technology from visual effects in advertising scenes for the purpose of communicating the idea to the recipient, which made the advertisement more attractive indeed about the focus of the viewer, attention and the ability to recall where it was Percentage of employing digital technologies to create virtual décor and visual and fictional effects by (52%) in advertising models.2- The digital technology gives the advertising image an expressive value by manipulating the dimensions of the virtual studio (visual effects) and makes the character perform its dramatic actions in the advertisement. The digital technology helped the director to employ characters and shapes that are not present in real life. Also, digital effects have the ability to create an atmosphere of tension. The viewer's attention is that the effects are one of the means of dazzling. The designer also focused on using non-existent characters who are dead in reality, and he used effect and optical illusions (42%(.Among the most important conclusions of the study: -Technology has the ability to create an impressionistic place within the real place by manipulating its construction, and this gives the advertisement an aesthetic value by means of modern technologies (Adobe After Effect)The production of the virtual studio in a way that attracts the eyes of the recipient, as the director and designer paid attention to the shape of the advertisement as well as the idea through the use of characters, shapes and drawings in the advertisement, as it worked to communicate the advertising idea to the spectator and also enabled the work of the virtual environments to suit the age group for which the advertisement was directed